Progress of the key materials for organic solar cells - Tong, Yang; Xiao, Zuo; Du, Xiaoyan; Zuo, Chuantian; Li, Yuelong; Lv, Menglan; Yuan, Yongbo; Yi, Chenyi; Hao, Feng; Hua, Yong; Lei, Ting; Lin, Qianqian; et al. (Science China-Chemistry, 2020)
Organic solar cells have attracted academic and industrial interests due to the advantages like lightweight, flexibility and roll-to-roll fabrication. Nowadays, 18% power conversion efficiency has been achieved in the state-of-the-art organic solar cells. The recent rapid progress in organic solar cells relies on the continuously emerging new materials and device fabrication technologies, and the deep understanding on film morphology, molecular packing and device physics. Donor and acceptor materials are the key materials for organic solar cells since they determine the device performance. The past 25 years have witnessed an odyssey in developing high-performance donors and acceptors. In this review, we focus on those star materials and milestone work, and introduce the molecular structure evolution of key materials. These key materials include homopolymer donors, D-A copolymer donors, A-D-A small molecular donors, fullerene acceptors and nonfullerene acceptors. At last, we outlook the challenges and very important directions in key materials development.
CRIS-Team WoS Importer:2020-04-21